2018
DOI: 10.1016/j.jweia.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Trains in crosswinds – Comparison of full-scale on-train measurements, physical model tests and CFD calculations

Abstract: Link to publication on Research at Birmingham portal General rights Unless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law. • Users may freely distribute the URL that is used to identify this publication. • Users may download and/or print one copy of the publication from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…It is acknowledged that there is always to some extent a difference between model-scale and full-scale results due to the disparity in Re. However, Re~10 5 has widely been regarded as a high enough value in which case the aerodynamic coefficients would be similar to those expected at full-scale, or at least the trend should be the same (Hong et al, 1998, Hargreaves and Morvan, 2007, Gallagher et al, 2018, Krajnović and Davidson, 2005b. Indeed, there is limited research available and therefore the Re effects are not conclusive, which requires more systematic study in the future.…”
Section: Truck Modelmentioning
confidence: 99%
“…It is acknowledged that there is always to some extent a difference between model-scale and full-scale results due to the disparity in Re. However, Re~10 5 has widely been regarded as a high enough value in which case the aerodynamic coefficients would be similar to those expected at full-scale, or at least the trend should be the same (Hong et al, 1998, Hargreaves and Morvan, 2007, Gallagher et al, 2018, Krajnović and Davidson, 2005b. Indeed, there is limited research available and therefore the Re effects are not conclusive, which requires more systematic study in the future.…”
Section: Truck Modelmentioning
confidence: 99%
“…The correctness and effectiveness of this system was proven by He et al 6 This system can separately and simultaneously measure the aerodynamic performances of the train and the bridge. Gallagher et al 28 confirmed that Re ¼ 1.4 Â 10 5 is enough to predict the side force coefficient of the train by comparing full-scale measurements and wind tunnel tests.…”
Section: Validation Of the Numerical Methodsmentioning
confidence: 96%
“…Gallagher et al. 28 confirmed that Re = 1.4 × 10 5 is enough to predict the side force coefficient of the train by comparing full-scale measurements and wind tunnel tests.
Figure 4.Comparison of the wind tunnel tests and numerical simulations: (a) experimental model, (b) measurement system, (c) bridge coefficients, and (d) train coefficients.
…”
Section: Validation Of the Numerical Methodsmentioning
confidence: 97%
“…There have been many pieces of research to estimate the aerodynamic behaviors of the train under a crosswind environment using the full-scale experiments, scaled wind tunnel tests and CFD simulations CONTACT Nan Zhang nzhang@bjtu.edu.cn (Alonso-Estébanez, Del Coz Díaz, Álvarez Rabanal, & Pascual-Muñoz, 2017;Baker, Jones, Lopez-Calleja, & Munday, 2004;Gallagher et al, 2018;Niu, Zhou, & Liang, 2018;Suzuki, Tanemoto, & Maeda, 2003). In these investigations, usually the train runs on the flat ground or embankment, and the movement of the train is created by means of the resultant velocity V r imposed on a static vehicle, as seen in Figure 1, depending on the train speed V t and incoming wind speed V w with a wind angle of α.…”
Section: Introductionmentioning
confidence: 99%
“…Based on all the problems mentioned above, it is necessary to study and discuss the aerodynamic characteristics of the train-bridge system with a moving train model. Generally known, it is difficult and complex to carry out a full-scale experiment to estimate the aerodynamic characteristics of the moving train owing to the unpredictable natural environment, expensive cost and long test period (Baker et al, 2004;Gallagher et al, 2018). For a scaled wind tunnel test in connection with a moving train, Baker (1986) initially developed a moving model rig to explore the forces on the advanced passenger train subjected to an atmospheric boundary layer and then, the train model accelerated by the gravity and traveling along the u-shaped guideway was applied by Bocciolone, Cheli, Corradi, Muggiasca, and Tomasini (2008).…”
Section: Introductionmentioning
confidence: 99%